Towards a structural understanding of drug and peptide transport within the proton-dependent oligopeptide transporter (POT) family. - Newstead, S (2011)
One of the principal aims of modern drug design is the targeted delivery of drugs within the body, such as to the central nervous system, combined with their exclusion from the liver and kidneys, which break down foreign molecules and subsequently eliminate them. Many of the commonly prescribed drugs are transported into cells and across the plasma membrane via endogenous membrane transporters, whose principal roles are the uptake of essential nutrients for metabolism. In many cases, such drug transport is serendipitous as they are simply mistaken as 'natural' compounds. Many of these transporters could, however, be targeted more efficiently, improving drug absorption, distribution and retention. The molecular details of these drug-transporter interactions, however, are at best poorly understood, in large part through the absence of any high-resolution structural information. To address this issue, we recently determined the structure of a prokaryotic peptide transporter, PepTSo from Shewanella oneidensis, which shares a high degree of sequence similarity and functional characteristics with the human PepT1 and PepT2 proteins. PepT1 and PepT2 contribute significantly to the oral bioavailability and pharmacokinetic properties of a number of important drug families, including antibiotics, antivirals and anticancer agents. The crystal structure of PepTSo provides the first high-resolution model of a drug importer and provides the starting point for understanding drug and peptide transport within the human body.